PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATERI MAKNA PANCASILA DI KELAS IV SDN 4 TEMULUS - Agustina, Ade Lia Norma; Rondli, Wawan Shokib; Ismaya, Erik Aditia (Universitas Muria Kudus, 2024)
There are identified problems in the teaching of Pancasila Education at SD N 4 Temulus, namely the lack of critical thinking skills among students. This study aims to examine whether there is a difference in the average scores between the pretest and posttest of students before and after learning using the Discovery Learning model on the critical thinking skills of 4th-grade students at SD N 4 Temulus. The research method is quantitative experimental with a One Group Pretest-Posttest design. The research sample consists of 15 students, comprising 5 female students and 10 male students. Data analysis uses the Shapiro-Wilk normality test and hypothesis testing with the Paired Sample T-Test. The results show a significance value of 0.00 0.05, indicating that the statistical test results are statistically significant. It can be concluded that there is a significant difference in the average scores between the pretest and posttest of students before and after learning using the Discovery Learning model on the critical thinking skills of 4th-grade students at SD N 4 Temulus.